Observations on the changes in status and movements of birds at the Middlesex Field Study Centre, Manjimup, Western Australia, based on twenty-five years of daily records - Brown, R.; Brown, M.; Davies, M.; Davies, Stephen (2005)
This paper presents a preliminary analysis of data recorded by R and M Brown on the occurrence of birds at the Middlesex Field Study Centre, Manjimup, between July 1974 and June 1999. During this period of twenty-five years daily records were kept of the presence or absence of 116 species of birds that visited the 2 hectare Home Farm and Home Dam of the Centre. During this time the number of records of 13 species increased, 33 decreased, 12 remained stable, 21 fluctuated and 5 increased and then decreased. A number of factors appeared likely to be correlated with the changes in status of the birds. These included the increasing salinity of the streams, the increase in the number of irrigation dams in the area, the changes in agricultural practice in the area with an increase in the number of vineyards and vegetable crops leading to increased use of herbicides and insecticides, the planting of an arboreatum at the Centre, the provision of additional nest boxes for swallows, the impact of myxomytosis and calici virus on rabbit numbers, and the road maintenance activities of the local shire. Rainfall records were maintained at the Centre and some changes in status appear to correlate with years of low rainfall. The data provide a useful base line for future studies of bird life in the area.